PENGARUH IMPLEMENTASI KEBIJAKAN KETERTIBAN UMUM TERHADAP EFEKTIVITAS PENERTIBAN PEDAGANG KAKI LIMA DI KOTA CIREBON - iskandar zulkarnaen (Universitas Swadaya Gunung Jati, 2014)
The main problem in this research are: effectiveness studies of street vendors in the city of Cirebon is still low, it is expected that the implementation of policies in public order has not been effective. Based on the above formulation of the problem, the research question is how much influence the implementation of policy on the effectiveness of public order policing of street vendors in the city of Cirebon? as well as how much influence the implementation of policy through the public order dimension implementation activities and communication between organizations, kerekteristik enforcement agencies, economic conditions, social and political, as well as the tendency of the effectiveness of the control apparatus peleksana street vendors in the city of Cirebon? The study was conducted by using Merode survey by taking samples and populations. Sebayak population 3036 people, taken a sample of 350 people. Data collection is done by means of literature study and field study (observational, waancara and questionnaires), while data analysis is done by using quantitative analysis Path Analysis (Path Analysis). The results of research that affects public order policy implementation large (54.5%) on the effectiveness of research padagang street in the city of Cirebon. Nevertheless, the effect is not optimal due to the increased effectiveness of pebertiban vendors after no more banayak public order felt by padagang pavement. Influence public order policy implementation is greater than the influence of other variables varriabel (45%), so that the effectiveness of the control of street vendors in the city of Cirebon more banayak influenced by public policy implementation.The dimensions of the implementation of development policy public order each berepengaruh the effectiveness of policing hawkers in the city of Cirebon. Kempat dimensions of public order policy, whose influence is greatest dimension is the economic, social and political (20.5%), then duusul by the influence of the dimensions of implementation activities and communication between organizations (13.8%), as well as the influence of the characteristics of the implementing agencies ( 11.6%). The dimensions of the smallest effect is the tendency of executive officers (8.6%). The influence of each dimension that cumulatively contribute to the magnitude of the inhabitants of the implementation of general policies by 54.5%.